2020
DOI: 10.21037/atm-20-6557
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of stock volatility and cardiovascular mortality: a systematic review and meta-analysis

Abstract: Background: Cardiovascular disease (CVD) and stroke are leading causes of death. It has several risk factors, including stress and pressure. Stock volatility can cause acute stress for stockholders so that it can cause CVD events. Recently, the spread of new coronaviruses worldwide has affected economic development greatly, leading to more severe stock market fluctuations, so we systematically quantify the short-term effect of stock volatility and CVD events.Methods: Time-series analysis on the effect of stock… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…And we concluded that the longitudinal observation sqrt(TG) had a time lag effect and cumulative effect on the disease outcome. This was unexpected and novel, as other studies had found lagged associations between some climatic factors, environmental factors as well as social factors and stroke onset [39][40][41]. The lag effect of dyslipidemia on stroke needed to be further explored.…”
Section: Discussionmentioning
confidence: 89%
“…And we concluded that the longitudinal observation sqrt(TG) had a time lag effect and cumulative effect on the disease outcome. This was unexpected and novel, as other studies had found lagged associations between some climatic factors, environmental factors as well as social factors and stroke onset [39][40][41]. The lag effect of dyslipidemia on stroke needed to be further explored.…”
Section: Discussionmentioning
confidence: 89%
“…And we concluded that the longitudinal observation sqrt(TG) had a time lag effect and cumulative effect on the disease outcome. This was unexpected and novel, as other studies had found lagged associations between some climatic factors, environmental factors as well as social factors and stroke onset [31][32][33]. The lag effect of dyslipidemia on stroke needed to be further explored.…”
Section: Discussionmentioning
confidence: 89%
“…However, some earlier studies concluded that the stock volatility had larger effects on elderly population. 34,35 This difference may be due to the different population characteristics and relatively small sample size in prior investigations. Similar to a recent study conducted in China, 10 our study indicated larger effect estimates among females, which might be partly explained by reduced fibrin clot lysability of coronary plaques for women compared with men.…”
Section: Discussionmentioning
confidence: 99%